Hubungan Pengetahuan dan Gaya Hidup dengan Kejadian Hipertensi di UPTD Puskesmas Bahagia Bekasi - Anita Wulandari; Cusmarih Cusmarih (Universitas Malahayati Lampung, 2024)
ABSTRACT Hypertension is a condition in which a person experiences an increase in blood pressure beyond normal limits that can cause pain or death. A person who is said to be hypertensive if blood pressure is more than the normal limit. Hypertension is also referred to as the silent killer where symptoms are often caused such as headaches, palpitations, heaviness in the nape, fatigue, blurred vision, buzzing ears. The purpose of conducting this study was to determine the relationship between knowledge and lifestyle with the incidence of hypertension at UPTD Puskesmas Bahagia Bekasi. Data collection by distributing questionnaire sheets, this research design is descriptive with a cross sectional approach. Based on the results of the analysis of 75 respondents that there were 19 (25.3%) respondents with the most knowledge in hypertension respondents there were 12 (16.0%) respondents, while there were 36 (48.0%) respondents who had the most knowledge in hypertension respondents there were 32 (42.7%) respondents, while there were 20 (26.7%) respondents with the most good knowledge in hypertension respondents there were 13 (17.3%) respondents. The results of the statistical test (chi square test) show that p value = 0.042 or p value a (0.05), so the conclusion is that Ho is rejected and Ha is accepted, which means that there is a relationship between knowledge and the incidence of hypertension. From the results of this study, it is expected for all patients and continue to check blood pressure regularly and is expected to change a healthy lifestyle. Keywords: Knowledge, Lifestyle, Hypertension ABSTRAK Hipertensi merupakan kondisi dimana seseorang mengalami peningkatan tekanan darah melebihi batas normal yang bisa menyebabkan kesakitan ataupun kematian. Seseorang yang dikatakan hipertensi apabila tekanan darah lebih dari batas normal. Hipertensi juga disebut juga sebagai silent killer dimana gejala yang sering ditimbulkan seperti sakit kepala, jatung berdebar-debar, rasa berat pada tengkuk, mudah lelah, pandangan kabur, telinga berdengung. Tujuan dalam melakukan penelitian ini adalah untuk mengetahui adanya hubungan pengetahuan dan gaya hidup dengan kejadian hipertensi di UPTD Puskesmas Bahagia Bekasi. Pengambilan data dengan menyebarkan lembar kuesioner, desain penelitian ini adalah deskriktif dengan pendekatan cross sectional. Berdasarkan hasil analisis 75 responden bahwa ada 19 (25.3%) responden dengan pengetahuan yang kurang terbanyak di reponden hipertensi ada 12 (16.0%) reponden, sedangkan ada 36 (48.0%) responden yang pengetahuan cukup terbanyak di responden hipertensi ada 32 (42.7%) responden, sedangkan ada 20 (26.7%) reponden yang pengetahuannya baik terbanyak di responden hipertensi ada 13 (17.3%) responden. Hasil dari uji statistic (chi square test) menunjukkan bahwa p value = 0,042 atau p value a (0,05), jadi kesimpulannya adalah Ho ditolak dan Ha diterima, yang artinya adanya Hubungan Pengetahuan Dengan Kejadian Hipertensi. Dari hasil penelitian ini, diharapkan bagi seluruh pasien dan tetap melakukan pemeriksaan tekanan darah secara rutin dan diharapkan untuk merubah pola hidup yang sehat. Kata Kunci: Pengetahuan, Gaya Hidup, Hipertensi